The role of Interleukin-33 in the development of idiopathic pulmonary fibrosis - Stephenson, Katherine (2021)
Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease characterised by the excessive deposition of extracellular matrix by fibroblasts and an irreversible loss of lung function. Recently, the interleukin (IL)-1 family member IL-33 has been implicated in the pathogenesis of IPF. Currently however, the cellular and molecular mechanisms by which IL-33 exerts its reported pro-fibrotic effects are poorly understood.